2003
DOI: 10.2320/matertrans.44.1461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nodular Graphite on the Deterioration of Vibration Fracture Resistance of Ferritic Cast Iron under an Aqueous Environment

Abstract: An intergranular fracture feature could be observed when ferritic spheroidal graphite cast irons were tested under continuously wet conditions. The maximum depth of intergranular fractures was closely related to the microstructural feature and ambient environment that caused the deterioration in vibration fracture resistance. Experimental evidence has confirmed the overall D-N curves can be generalized into three characteristic regions. Intergranular fractures occurred in the vicinity of the surface; the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…More important, Martinez et al [15] further reported reduction of ductility by 73-83% in water, 29-47% in SAE 30 mineral lubricant oil, and 67% in isopropyl alcohol (99%). Other studies [10][11][12][13][14]16] reported similar results. Furthermore, several authors [10,11] reported that this phenomenon is revertible, that is, after drying, the specimens revert to their previous tensile properties.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…More important, Martinez et al [15] further reported reduction of ductility by 73-83% in water, 29-47% in SAE 30 mineral lubricant oil, and 67% in isopropyl alcohol (99%). Other studies [10][11][12][13][14]16] reported similar results. Furthermore, several authors [10,11] reported that this phenomenon is revertible, that is, after drying, the specimens revert to their previous tensile properties.…”
Section: Introductionsupporting
confidence: 67%
“…To further distinguish investigated ADI materials in dry condition compared to materials used in literature [10][11][12][13][14][15][16], impact test and hardness were determined. The impact energy was measured for as-cast ductile iron and ADI material in dry condition on unnotched Charpy specimens (10 × 10 × 55 mm) using a Charpy impact testing machine Schenck-Treble RPSW/A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2) To effectively improve the quality of the castings and reduce the amount of rejected materials, rapidly monitoring the graphite shape of cast iron is becoming very important.…”
Section: Introductionmentioning
confidence: 99%